Head Circumference Features of Under One Year Old Children at Dr. Pirngadi Hospital Medan - Yulitas Bahtiar; Marisi Manurung; Manihar D. Marbun; Iskandar Z. Lubis; Bistok Saing (Indonesian Pediatric Society, 1992)
A descriptive cross sectional study to have normal values of the bead circumference of under one year old children in Dr. Pirngadi Hospital Medan had been done during january to February 1990. The sample size determined based on formula, was 356 (178 boys and 178 girls). Each sex group was devided proportionally by age in months. Only children with good nutritional status and middle to high socio economic level were included in this study. The mean value of the head circumference is still in the range of the mean of Nellhaus standard. Tbe Nellhaus standard can be used as a standard of bead circumference of under one year old children at Dr. Pirngadi Hospital Medan.